Effect of different soil mixtures on growth of teak (Tectona grandis Linn.f.) seedlings - Mehta, Pradeep; Rana, B.S.; Parihar, A.K.S.; Baksh, Hari (Indian Journal of Agroforestry, 2020)
This study was carried out to ascertain changes in growth and dry weight of nursery raised teak (Tectona grandis) seedlings by using varied proportions of soil, sand and farmyard manure in soil mixture under sodic soil condition. It was noticed that increase in proportion of sand in the soil mixture (1:1 to 1:2 soil and sand ratio) showed increase in seedling growth. However, seedlings assumed rapid growth when FYM was added to the soil having greater amount of sand (1:3:2; soil: sand: FYM).